THE CURRICULAR IMPLEMENTATION OF FOLK MUSIC PARADIGMS: THE COMPARATIVE ANALYSIS OF THE 1981 AND 1999 CURRICULA OF FOLK MUSIC EDUCATION IN HUNGARY - BÍRÓ, István Ferenc (Studia Universitatis Babes-Bolyai Musica, 2018)
Due to the planned renewal of the Hungarian folk music education, the curricula related to folk-related education (Bolya, 2017) have recently received a new focus. In our comparative curriculum analysis, we examine curricula related to folk music education from 1981 to 1999 with the method of document analysis. We have supplemented our basic method, especially in the initial and informational phase of the research, with the method of questioning. With our formulated research questions, we would like to highlight the educational backgrounds related to institutional folk music education, which will help us to get closer to determine the time of the demand for the original application method of folk music at institutional levels. With our chosen methods, we reveal deeper, more differentiated relationships, as paradigm shift related to authenticity becomes visible not only at the curriculum level but also differences in the curriculum are drawn up. As a result of our comparative analysis, it can be stated that the curriculum of 1999 was a paradigm shift in curriculum level in the field of folk music education, but in the case of core subjects (bagpipe and partly hurdy-gurdy) of the 1981 curriculum some exceptions can be identified, the folk music perception of which exceeds that of the other core subjects.